Competition, Competitiveness and Growth in Sub-Saharan Africa - Cherif, Reda (IMF Working Papers; Working Paper ;, 2020)
Does greater product market competition improve external competitiveness and growth? This paper examines this question by using country-and firm-level data for a sample of 39 sub-Saharan African countries over 2000-17, as well as other emerging market economies and developing countries, and finds that an improvement in domestic competition is associated with a signficant increase in real GDP per capita growth rate, achieved mainly through an improvement in export competitiveness and productivity growth. Price levels, including of essential items, are also generally lowered with an increase in competition. Moreover, at the firm-level, evidence shows that greater competition-proxied through a decline in corporate market power-is associated with an increase in firm's investment and the labor's share in output. These effects are more pronounced in the manufacturing sector and among domestic firms compared to foreign firms.